Two Cases of Myeloproliferative Neoplasm with a Concurrent JAK2V617F Mutation and BCR/ABL Translocation without Chronic Myelogenous Leukemia Phenotype Acquisition during Hydroxyurea Treatment - Park, Sang Hyuk; Chi, Hyun-Sook; Cho, Young-Uk; Jang, Seongsoo; Park, Chan-Jeoung; Kim, Dae-Young; Lee, Je-Hwan; Lee, Kyoo-Hyung (Annals of laboratory medicine, 2013)
KCI Citation Count: 5